Pemikiran Politik Islam Ahmad Hassan Perspektif Politik Islam Indonesia - Muh. Rifa’i (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article analyzesthe Islamic political thought of Ahmad Hasan within the political perspective of Indonesia Islam. According to Hassanâ€™s point of view, Islam is a complete religion which regulates all aspects of human life ranging from spiritual to politics. For the sake of establishing an Islamic state in accordance with the will of God, Muslims should carry out all of the Islamic teachings in every situation of life. Laws and regulations in accordance with al-Qurâ€™an should be implemented. Islam, for him, is another option of a national ideology that considers no place for religion. He wants Islam to regulate all aspects of human life, based on the belief that Islam is the absolute truth. Islam is seen as something of the highest and widest beyond national boundaries and lines. Thus, Hassan is considered a fundamentalist thinker. In the struggle for the enforcement of Islamic Shariâ€™ah, he wants to transform the Islamic community to its original root. He firmly believed that Muslims in Indonesia are infected by spiritual disease which ought to be cured with a radical revolutionary way. Thus, he suggested, that at personal level, a Muslim should apply the Islamic law in every place and every time. Keywords: Ahmad Hassanâ€™s thought, concept of political Islam, Islamic political development in Indonesia Â Abstrak: Artikel ini mempresentasikan tentang pemikiran politik Islam menurut Ahmad Hasan dalam perspektif politik Islam Indonesia. Dalam pandangan Ahmad Hassan, Islam adalah agama yang lengkap yang mengatur sendi-sendi kehidupan manusia mulai dari karohanian sampai masalah politik kenegaraan. Demi mewujudkan suatu negara Islam yang sesuai dengan yang dikehendaki Tuhan, maka kaum muslimin harus melaksanakan seluruh ajaran agama Islam di setiap sendi kehidupan. Undang-undang dan peraturan-peraturan yang sesuai dengan al-Qurâ€™an harus dilaksanakan. Pemerintahan Islam baginya adalah pilihan lain dari faham kebangsaan yang dianggapnya sebagai tidak memberikan tempat bagi agama. Ia menginginkan Islam memasuki seluruh aspek kehidupan manusia, sesuai dengan keyakinan bahwa kebenaran ajaran Islam adalah mutlak. Islam dipandang sebagai sesuatu yang tertinggi dan terluas menerjang batas-batas kebangsaan dan ketanah-airan. Ahmad Hassan adalah seorang pemikir yang fundamentalis, dalam memperjuangkan tegaknya syari'at Islam, Ahmad Hassan ingin mengubah masyarakat Islam sampai ke akar-akarnya, dan ingin menghancurkan penyakit umat Islam dengan cara yang radikal secara revolusioner, secara jelas, tanpa samar-samar dan penuh kepastian. Suka atau tidak suka, menurut Ahmad Hassan, seorang muslim harus menggunakan hukum Islam di setiap tempat dan setiap hal.